"It is not the diet; it is the mental part we need help with." A multilevel analysis of psychological, emotional, and social well-being in obesity. Issue 1 (1st January 2017) - Rand, Kathryn; Vallis, Michael; Aston, Megan; Price, Sheri; Piccinini-Vallis, Helena; Rehman, Laurene; Kirk, Sara F.L.
ABSTRACT: In this research, we explored the psychological, emotional, and social experiences of individuals living with obesity, and perceptions of health care providers. We conducted a theoretical thematic analysis using two theoretical frameworks applied to transcripts from a previous qualitative study. Themes from a mental well-being framework were subsequently categorized under five environmental levels of the Social-Ecological Model (SEM). Key mental well-being themes appeared across all levels of the SEM, except the policy level. For the individual environment, one main theme was food as a coping mechanism and source of emotional distress. In the interpersonal environment, two themes were (a) blame and shame by family members and friends because of their weight and (b) condemnation and lack of support from health professionals. In the organizational environment, one main theme was inadequate support for mental well-being issues in obesity management programmes. In the community environment, one major theme the negative mental well-being impact of the social stigma of obesity. An overarching theme of weight stigma and bias further shaped the predominant themes in each level of the SEM. Addressing weight stigma and bias, and promoting positive mental well-being are two important areas of focus for supportive management of individuals living with obesity.